Liver Transplantation for Monogenic Metabolic Diseases Involvingthe Kidney (Journal of Renal and Hepatic Disorders, 2017)
Several metabolic monogenic diseases may be cured by liver transplantation alone (LTA) or by combined liver–kidney transplantation (CLKT) when the metabolic disease has caused end-stage renal disease. Liver transplantation may be regarded as a substitute for an injured liver or as supplying a tissue that may replace a mutant protein. Two groups of diseases should be distinguished. In the first group, the kidney tissue may be severely damaged while the liver tissue is almost normal. In this group, renal transplantation is recommended according to the degree of renal damage and liver transplantation is essential as a genetic therapy for correcting the metabolic disorder. In the second group, the liver parenchymal damage is severe. In this group, liver transplantation is essential to avoid liver failure. LTA may also avoid the progression of the renal disease; otherwise a CLKT is needed. In this review, we describe monogenic metabolic diseases involving the kidney that may have beneficial effects from LTA or CLKT. We also highlight the limitations of such procedures and the choice of alternative medical conservative treatments.
Keywords: atypical hemolytic uremic syndrome; glycogen storage disease; monogenic metabolic diseases; organic acidurias; primary hyperoxaluria